Studies on solution – growth thin films of CdS : Zn for photovoltaic application (Baghdad Science Journal, 2009)
Structural, optical, and electrical properties of thin films of CdS : Zn prepared by the solution – growth technique are reported as a function of zinc concentration. CdS are window layers influencing the photovoltaic response of CIS solar cells. The zinc doping concentration was varied from 0.05 to 0.5 wt %, zinc doping apparently increase the band gap and lowers the resistivity. All beneficial optical properties of chemically deposited CdS thin films for application as window material in heterojunction optoelectronic devices are retained. Heat treatment in air at 400 °C for 1h modify crystalline structure, optical, and electrical properties of solution growth deposited CdS : Zn films.